POLA ASUH ORANG TUA SANTRI TAHFIZ HUBUNGANNYA DENGAN RELIGIUSITAS DAN KEPRIBADIAN - Nurjannah, Nurjannah; Faridah, Hidayatul (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2022)
It is a challenge for children and parents whose children have dual education, general formal as well as religious education. These challenges include having to manage time, energy and learning activities, in this case parents are required to have extra parenting methods for the success of their children. This study aims to determine the relationship between parenting patterns of tahfiz students with religiosity and personality. The research subjects consisted of 51 parents of students of Tahfiz Gemilang Children and Toddlers, Sleman Regency, Yogyakarta. The research was carried out with mixed methods with quantitative survey research as the main research complemented by qualitative research to explore the findings. The main data collection tool is a questionnaire, equipped with interviews and observations. Multiple linear regression analysis was used to determine the relationship between parenting patterns with religiosity and personality. The results of the hypothesis test prove that there is a significant relationship between parenting patterns of tahfiz students with religiosity and personality with a value of a=54,313; religiosity variable regression coefficient 0.412; and the regression coefficient value of the personality variable is 0.593. The results of the coefficient of determination (R Square) showed that religiosity and personality contributed 25.9% to the parenting pattern of tahfiz students. This study also found that the parenting pattern of tahfiz students was dominated by the authoritarian type (66.7%). This is suspected to be the impact of most of the parents of tahfiz students with a general education background (78.43%) whose religious orientation is of an extrinsic type which tends to be formalistik and rigid. Keywords: Parenting Pattern, Tahfiz Students, Religiosity, Personality